A Numerical Method for Dynamic Wetting Using Mesoscopic Contact-Line Models (Communications in Computational Physics, 2024)
Numerical simulation of wetting or dewetting processes is challenging dueto the multiscale feature of the moving contact line. This paper presents a numericalmethod to simulate three-dimensional wetting processes in the framework of lubrication equation and Navier slip condition. A mesoscopic model of the moving contactline is implemented with a cutoff of the computational domain at a small distancefrom the contact line, where boundary conditions derived from the asymptotic solution of the intermediate region are imposed. This procedure avoids the high resolutionrequired by the local interface near the contact line and enables the adoption of physically small slip lengths. We employ a finite element method to solve the lubricationequation, combined with an arbitrary Lagrangian-Eulerian method to handle the moving boundaries. The method is validated by examining the spreading or sliding of aliquid drop on the wall. The numerical results agree with available exact solutions andapproximate theories.
Keywords: Moving boundary problem; moving contact line; wetting; lubrication equation.